Smart sensors for industrial applications - Iniewski, Krzysztof (Devices, circuits, and systems, 2013)
"This book assembles the latest research in the field of smart sensors technology in one place. It exposes readers to myriad applications that smart sensors technology has enabled. The book is meant for advanced graduate research work or for academicians and researchers. This way the book has a widespread appeal, including practicing engineers, academicians, research scientists and senior graduate students"--